HD-RNAS: An Automated Hierarchical Database of RNA Structures - Ray, Shubhra Sankar; Halder, Sukanya; Kaypee, Stephanie; Bhattacharyya, Dhananjay (Frontiers in Genetics, 2012)
One of the important goals of most biological investigations is to classify and organize the experimental findings so that they are readily useful for deriving generalized rules. Although there is a huge amount of information on RNA structures in PDB, there are redundant files, ambiguous synthetic sequences etc. Moreover, a systematic hierarchical organization, reflecting RNA classification, is missing in PDB. In this investigation, we have classified all the available RNA crystal structures from PDB through a programmatic approach. Hence, it would be now a simple assignment to regularly update the classification as and when new structures are released. The classification can further determine (i) a non-redundant set of RNA structures and (ii) if available, a set of structures of identical sequence and function, which can highlight structural polymorphism, ligand-induced conformational alterations etc. Presently, we have classified the available structures (2095 PDB entries having RNA chain longer than 9 nucleotides solved by X-ray crystallography or NMR spectroscopy) into nine functional classes. The structures of same function and same source are mostly seen to be similar with subtle differences depending on their functional complexation. The web-server is available online at http://www.saha.ac.in/biop/www/HD-RNAS.html and is updated regularly.